Ч. 3: Оптика. Атомная и ядерная физика; Физика. Сборник задач (с решениями) - Тюрин Ю. И. Юрий Иванович; Ларионов В. В. Виталий Васильевич; Чернов И. П. Иван Петрович; Ефремова Н. А. Наталья Александровна; Кузнецов С. И. Сергей Иванович; Купрекова Е. И. Елена Ивановна; Лельчук Л. Ю. Лариса Юрьевна; Рудковская В. Ф. Вера Федоровна; Семкина Л. И. Людмила Иосифовна; Сивов Ю. А. Юрий Александрович; Толмачева Н. Д. Нелла Дмитриевна; Хоружий В. Д. Владимир Дмитриевич (2010, 2010)
Заглавие с титульного экрана